ЗАМОНАВИЙ ТИЛШУНОСЛИКДА ТЕРМИННИ ТАЪРИФЛАШНИНГ ТУРЛИ ЁНДАШУВЛАРИ - Ходжаева, Д.И. (SCIENCE and SOCIETY, 2020)
The given article deals with different approaches to defining terms, such as normative, descriptive and others. The main features and peculiarities of terms are also studied in the article.
Keywords: term; normative; descriptive; lexical-semantic; terminological system; terminological field; monosemy